The Influence of Total Quality Management, Lean Manufacturing, and Entrepreneurial Orientation on Operating Performance in Semarangan Batik Entrepreneurs in Semarang City - Sutrimono, Sutrimono; Maghribi, Maulana (Review: Journal of Multidisciplinary in Social Sciences, 2024)
Operations management is very important for the production process, the performance it produces is very important for the sustainability of the company. Further research is needed because of the many production problems faced by batik craftsmen in Semarang City. This study aims to study how the application of Total Quality Management, entrepreneurial orientation, and Lean Manufacturing impacts on operating performance. This study used questionnaires as a data collection method. Simple random sampling was used to select the sample, and 59 people were selected. Multiple linear regression analysis was used to evaluate the effect of the independent variable on the dependent variable of the study. The results showed that total quality management improved operating performance (H1 received). The second hypothesis says Lean Manufacturing improves operations performance is accepted, and the third hypothesis says entrepreneurial orientation improves operations performance is accepted. The results of the coefficient of determination test show that the three independent variables affect operating performance by 53%. It is recommended to Semarang batik craftsmen in Semarang City to provide training to their employees, improve their production methods, and reduce their dependence on intermediaries in sales.